Outcome of left main stem percutaneous coronary intervention in a UK nonsurgical center: A 5‐year clinical experience. Issue 3 (11th February 2021) - Alaour, Bashir; Onwordi, Eunice; Khan, Asif; Menexi, Christina; Carta, Sabrina; Strike, Philip; Griffiths, Huw; Anantharam, Brijesh; Hobson, Alexander; Dana, Ali
Abstract: Objectives: To evaluate the outcome of unprotected left main stem (LMS) percutaneous coronary intervention (PCI) in a large UK nonsurgical center. Background: PCI on unprotected LMS is increasingly regarded as a viable alternative to coronary artery bypass grafting (CABG) with comparable outcome and safety profile in select groups. The safety and efficacy of unprotected LMS PCI without on‐site surgical back up has not been reported. Methods: Data on all unprotected LMS PCI performed between January 2011 and December 2015, was collected from the local PCI database and electronic patient records. In hospital and 1‐year major adverse cardiovascular events (MACE) (all‐cause mortality, myocardial infarction [MI], stroke, and target vessel revascularization [TVR]) was recorded. Results: 249 patients had unprotected LMS intervention during the study period. 77% of patients ( n = 192) were male and mean age was 70 ± 12 years. 31% ( n = 78) of cases were elective, 44% ( n = 109) NSTEMI, and 25% ( n = 62) STEMI. Anatomical distribution: 19% ( n = 47) ostial left main, 31% ( n = 77) shaft, and 50% ( n = 125) bifurcation. The mean SYNTAX score was 24.4 ± 10.6. 22% ( n = 55) of patients had severe LV impairment preprocedure and 13% ( n = 33) were in cardiogenic shock at presentation. 35% (14%) required IABP support. The vast majority (98.4%) of procedures were successful. No patients required emergency transfer for CABG surgery. There were 25 (10%) in‐hospital deaths. 68% of in‐hospital deaths occurred in patients undergoing primary PCI for STEMI. 72% of patients who died were in cardiogenic shock at presentation. The 12‐month MACE rate was 17.2%. Death occurred in 11.6%, MI in 2.4%, TVR in 2.4%, and stroke in 0.8% of patients. Conclusion: These results highlight the safety and efficacy of unprotected LMS PCI in a high volume non‐surgical center.